Feasibility Study on Raising the Operation Speed of EMU from 350 km/h to 400 km/h - Lei WANG; Dongming YU; Yong DING (机车电传动)
In order to further improve people's travel experience and service quality, improve transportation organization efficiency and reduce operation cost, CRRC Changchun Railway Vehicles Co., Ltd. plans to develop 400 km/h high-speed EMU. Based on the research results of "Key technologies of high-speed passenger transport equipment with speed of 400 km/h and above", which was the key project of "advanced rail transit" of the ministry of science and technology of China, this paper mainly discussed the feasibility of raising the operation speed of EMU from 350 km/h to 400 km/h from the perspective of operation capacity, safety, comfort and economy.